PERANAN PEMBELAJARAN GEOGRAFI DALAM PEMBENTUKAN SIKAP PESERTA DIDIK TERHADAP MITIGASI BENCANA GEMPA BUMI DAN LONGSOR DI KOTA PADANG - Novarita, Amalia; Sugandi, Dede; Pasya, Gurniwan Kamil (Universitas Pendidikan Indonesia, 2015)
Padang are subduction plate zone between Hindia-Austalia and Eurasia, its about 200 km from west off the coast of Padang. This condition makes Padang on high risk on dealing natural disaster issue such as earthquake which triggered landslide that cuts road in Padang and create chaos for people around. Geography are needed for student to acknowledged the things that happen before and after disaster and called disaster mitigation to create human behavior when such disaster happen around them, especially for student. Research conducted in public and private high school in Padang. Samples takes 11 schools picked randomly using random sampling. Research being process using descriptive research. And the results are students in Padang did not aware the importance of learning about mitigation disaster for now. It means with a lot of things happens, students didnât prepare their self in order to prevent any huge damage of disaster due to lack of information about it. When questioner being spread around the student it was found out that they feel hesitant on behavior during mitigationÂ disaster. Therefore it is really important for teacher to inform, teach, train and create studentâs behavior to minimizing any risk before, during and after earthquake and landslide happens.